Economic Growth and Inflation: Evidence from Indonesia - Mas Rangga Cili; Barkah Alkhaliq (Signifikan: Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the relationship of economic growth with inflation in Indonesia between 2010 and 2014. The research method uses static data panel analysis with economic growth as the dependent variable and inflation, investment, and population as independent variables. Research shows that inflation, investment, and population, where the three variables have the same aim (positive) relationship with economic growth. The effect of investment on economic growth is more significant than inflation on economic growth. The positive relationship between inflation and economic relations shows that inflation can increase economic growth. This can be maintained if the government represented by Bank Indonesia can always keep inflation at a low/mild level. Inflation targeting policy needs to be maintained by referring to the inflation targeting of previous years.How to Cite:Cili, M. R., & Alkhaliq. (2022). Economic Growth and Inflation: Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 145-160. https://doi.org/10.15408/sjie.v11i1.19848.